SoTL in 60: Session 10: Sarah Bunnell (Elon University) and Joshua Hill (MRU), interviewed by Sally Haney - Haney, Sally (Imagining SoTL, 2025)
The keynote speakers connect! Attendees at the Banff SoTL Symposium were treated to a provocative opening keynote by Sarah Bunnell (Elon) and an equally inspiring closing keynote by Joshua Hill (MRU). Sarah and Josh dropped by the podcasting table just before Josh's closing address. Thank you, both, for sharing your ideas, your time, and your service to higher education.